Early graft failure of GalTKO pig organs in baboons is reduced by expression of a human complement pathway‐regulatory protein. (14th July 2015) - Azimzadeh, Agnes M.; Kelishadi, Sean S.; Ezzelarab, Mohamed B.; Singh, Avneesh K.; Stoddard, Tiffany; Iwase, Hayato; Zhang, Tianshu; Burdorf, Lars; Sievert, Evelyn; Avon, Chris; Cheng, Xiangfei; Ayares, David; et al.
Abstract We describe the incidence of early graft failure (EGF, defined as loss of function from any cause within 3 days after transplant) in a large cohort of GalTKO pig organs transplanted into baboons in three centers, and the effect of additional expression of a human complement pathway‐regulatory protein, CD46 or CD55 (GalTKO.hCPRP). Baboon recipients of life‐supporting GalTKO kidney (n = 7) or heterotopic heart (n = 14) grafts received either no immunosuppression (n = 4), or one of several partial or full immunosuppressive regimens (n = 17). Fourteen additional baboons received a GalTKO.hCPRP kidney (n = 5) or heart (n = 9) and similar treatment regimens. Immunologic, pathologic, and coagulation parameters were measured at frequent intervals. EGF of GalTKO organs occurred in 9/21 baboons (43%). hCPRP expression reduced the GalTKO EGF incidence to 7% (1/14; P < 0.01 vs. GalTKO alone). At 30 mins, complement deposits were more intense in organs in which EGF developed (P < 0.005). The intensity of peri‐transplant platelet activation (as β‐thromboglobulin release) correlated with EGF, as did the cumulative coagulation score (P < 0.01). We conclude that (i) the transgenic expression of a hCPRP on the vascular endothelium of a GalTKO pig reduces the incidence of EGF and reduces complement deposition, (ii) complement deposition and platelet activation correlate with early GalTKO organ failure, and (iii) the expression of a hCPRP reduces EGF but does not prevent systemic coagulation activation. Additional strategies will be required to control coagulation activation.